Medical student's view of humanized childbirth in mageense maternity: learning and Merleau-Ponty (Research, Society and Development, 2020)
The  aim  of  the  study  was  to  capture  the  perception  of  medical  students  regarding childbirth in a hospital unit of the Unified Health System focusing on the humanization of their praxis  in the city of Magé / Rio de Janeiro, where the implementation of the National Humanization Policy is incipient. . The philosophical framework was based on Maurice Merleau-Ponty. It was a qualitative study in which, through an interview based on phenomenology with eighteen medical students, from master's dissertation data  at the Fluminense Federal University, it was possible to analyze their experience in relation to the  learning  of  humanized  childbirth.  After  approval  by  a  specific  Research  Ethics Committee (opinion number 2,872,462), a phenomenological interview was conducted. The  students  rated  the  quality  of  normal  childbirth  learning  in  the  health  facility  as satisfactory; however, they pointed to the difficulty of putting humanization into practice, given the high demand for care. It was not contemplated the humanization that imposes look  and  communication  with  the  other.  The  analysis  of  the  perception  of  others rediscovers the difficulty that the cultural world raises, according to Merleau-Ponty, and thus there is a lapse in the graduation of  physician regarding the construction of empathy as an element of humanization. Practical practice in Obstetrics should therefore involve not only theoretical knowledge, but also humanization of childbirth and  understanding of  sociocultural context of pregnant women.